Pengaruh Kepemilikan Institusional Terhadap Pengungkapan ESG Dengan Kinerja Keuangan Sebagai Variabel Moderasi - Putri, Yulia Ananda; Nugraha, Adri Putra (Jurnal Akuntansi & Keuangan Unja, 2026)
This study aims to examine the effect of institutional ownership on Environmental, Social, and Governance (ESG) disclosure, with financial performance as a moderating variable. The research was conducted on companies listed in the ESG Quality 45 IDX KEHATI index for the 2021–2023 period using secondary data. A quantitative method with Structural Equation Modelling-Partial Least Square (SEM-PLS) was employed for analysis. The findings reveal that institutional ownership has a positive and significant effect on ESG disclosure as well as on financial performance. However, financial performance is not proven to moderate the relationship between institutional ownership and ESG disclosure. These results emphasize that institutional ownership plays a crucial role in enhancing ESG reporting transparency, while financial performance does not necessarily strengthen the relationship between institutional ownership and ESG disclosure.